Traditional health practitioners and sustainable development: a case study in South Africa. (December 2018) - Street, R.A.; Smith, M.; Moshabela, M.; Shezi, B.; Webster, C.; Falkenberg, T.
Abstract: Objectives: To highlight legal and regulatory advances relating to South African traditional health practitioners (THPs) over the past 10 years and discuss the implications for the translation of health policies into guidelines for sustainable practice supporting public health. Study design: This is a rapid, structured literature review. Methods: A rapid, structured literature review was undertaken to identify relevant studies related to South African THPs involving a search of peer-reviewed literature from three databases and a grey literature internet search. The identified citations were screened, critically appraised, and narratively synthesized. Results: Efforts to regulate THPs in South Africa are underway; however, the lack of a regulatory framework for traditional practices is hampering progress. Several efforts to collaborate with THPs have been made over the years, many of which were not systematically evaluated and not based on principles of mutual respect. Existing collaborative examples need to be further supported by cost-effective evidence to suit the South African public health budget. Furthermore, small collaborative research efforts do not take into consideration the scale up of interventions. Conclusions: THPs in South Africa represent an important healthcare resource. However, the current policy environment does not support indicators to describe, monitor, and/or evaluate the role of THPs in the healthcare system. Highlights: Regulation of traditional health practitioners (THPs) in South Africa is underway. The number of THPs testifies to the importance and resilience of their practice. Focused public health policies of THPs in health care are lacking.